2015
DOI: 10.1902/jop.2015.150083
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytic Sclerostin Expression in Alveolar Bone in Rats With Diabetes Mellitus and Ligature‐Induced Periodontitis

Abstract: Enhanced alveolar bone loss, suppressed bone formation, and prevalent TNF-α expression were characteristic of the DP group compared with the P group. Suppressed bone formation in the DP group was observed simultaneously with increased sclerostin and TNF-α expression. These results suggest that upregulated osteocytic sclerostin expression in periodontitis accompanied by DM may play a role in suppressed bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…Hyperglycaemia increased SOST at mRNA and protein levels in osteoblast lineage cells (Kang et al., ). The gene expression of SOST was upregulated in the tibia of rats with type 2 DM (Hie, Iitsuka, Otsuka, & Tsukamoto, ; Nuche‐Berenguer et al., ), and the number of SOST‐positive osteocytes was increased in rats with DM and periodontitis (Kim et al., ). Furthermore, patients with type 2 DM present higher circulating levels of SOST than non‐diabetic subjects (García‐Martín et al., ; Gaudio et al., ; Gennari et al., ) and an association between elevated systemic levels of SOST and the risk of fractures (Yamamoto, Yamauchi, & Sugimoto, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperglycaemia increased SOST at mRNA and protein levels in osteoblast lineage cells (Kang et al., ). The gene expression of SOST was upregulated in the tibia of rats with type 2 DM (Hie, Iitsuka, Otsuka, & Tsukamoto, ; Nuche‐Berenguer et al., ), and the number of SOST‐positive osteocytes was increased in rats with DM and periodontitis (Kim et al., ). Furthermore, patients with type 2 DM present higher circulating levels of SOST than non‐diabetic subjects (García‐Martín et al., ; Gaudio et al., ; Gennari et al., ) and an association between elevated systemic levels of SOST and the risk of fractures (Yamamoto, Yamauchi, & Sugimoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TNF‐α and IL‐1ß induce the expression of DKK‐1 and SOST in systemic conditions (Baek et al., ; Choe et al., ; Heiland et al., ; Kim et al., ; Wang et al., ). The upregulation of TNF‐α occurred simultaneously with the increase in SOST in diabetic rats with periodontitis (Kim et al., ) and together with increases in SOST and DKK1 in CP in humans (Napimoga et al., ). Notably, DKK1 and SOST inversely correlated with IL‐6 in the control group at mRNA level and in the DM group at protein level, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathological conditions, sclerostin expression is altered in response to inflammatory molecules such as TNFα. Recently, a study using a rat model of ligature‐induced periodontitis revealed significant increases in sclerostin expression in osteocytes during the early and destructive phase of the disease . Interestingly, the rise in sclerostin levels was associated with a similar increase in RANKL production.…”
Section: Effects Of Tumour Necrosis Factor‐α On Osteocytes and Their mentioning
confidence: 99%
“…Osteocyte secretion of sclerostin is acutely regulated by mechanical loading [57] and by a variety of physiologic conditions, some leading to decreased sclerostin levels (i.e., mechanical loading, high PTH [58, 59], high estrogen [60, 61]) and some leading to increased sclerostin levels (i.e., mechanical unloading [61, 62], advancing age [60, 61, 63], skeletally detrimental drugs [64]). In T1D, as expected for a disease characterized by lower bone formation and Wnt-signaling inhibition, [10] increases in sclerostin gene expression [10, 65] have been reported, in vivo , in STZ-induced diabetic rats [65]. Moreover, in vitro , osteocytes treated with high glucose (22 mM [66] or 30 mM [67]) or with advanced glycation end-products (AGEs) [66] exhibit increased expression of sclerostin protein and mRNA, along with osteocyte apoptosis [66].…”
Section: Effects Of Type 1 Diabetes On Osteocytesmentioning
confidence: 99%